2020
DOI: 10.1111/eci.13248
|View full text |Cite
|
Sign up to set email alerts
|

High‐sensitivity cardiac troponin T 30 days all‐come mortality in patients with acute heart failure. A Propensity Score‐Matching Analysis Based on the EAHFE Registry. TROPICA4 Study

Abstract: Background: Acute heart failure (AHF) patients with high troponin levels have a worse prognosis. High-sensitive troponin T (hs-TnT) has been used as a tool to stratify prognosis in many scales but always as a qualitative and not as a quantitative variable. Objectives: The main objective of this study was to determine the best hs-TnT cutoff for prediction of 30-day all-cause mortality. Methods: The EAHFE registry, a prospective follow-up cohort of patients with AHF, was analysed. We performed a propensity score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…The c-statistic of troponin alone in predicting in-hospital mortality was higher than those recently reported for 30-day mortality of patients with congestive heart failure, 9 atrial fibrillation or cardiovascular hospitalizations, 10 and syncope for cardiac arrhythmias. 11 The models in these studies [9][10][11] had odds ratios of 2.95, 1.85, and 2.35, respectively, for elevated troponin test values with c-statistics of 0.70, 0.714, and 0.69. These studies did not test the predictive value of models including age and admission laboratory tests without troponin.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The c-statistic of troponin alone in predicting in-hospital mortality was higher than those recently reported for 30-day mortality of patients with congestive heart failure, 9 atrial fibrillation or cardiovascular hospitalizations, 10 and syncope for cardiac arrhythmias. 11 The models in these studies [9][10][11] had odds ratios of 2.95, 1.85, and 2.35, respectively, for elevated troponin test values with c-statistics of 0.70, 0.714, and 0.69. These studies did not test the predictive value of models including age and admission laboratory tests without troponin.…”
Section: Discussionmentioning
confidence: 88%
“…Studies that found an increased short-term mortality risk in patients with elevated troponin values did not explore its additive value to that of other risk indicators 9–11 . The present study attempts to determine whether troponin values improve the prediction of in-hospital mortality of older adult patients without suspected ACS above that of a model that includes age and routine admission laboratory tests.…”
mentioning
confidence: 93%
“…Parissis et al identified a ROC optimized hsTnT cut-off of 77 ng/l to predict all-cause mortality with a sensitivity of 62% and specificity of 72% in patients with predominantly reduced LV-EF [ 27 ]. Roset et al found a ROC optimized hsTnT cut-off of 35 ng/l with a sensitivity of 67% and specificity of 56% in a population consisting of both HFrEF and HFpEF [ 28 ]. The difference in cut-offs among these studies may be due to the assessment of different patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there was a tendency toward an increased risk of mortality in patients with high levels of AG [odds ratio (OR) = 1.42, p = 0.092]. Moreover, according to the evidence derived from the Epidemiology of Acute Heart Failure in Emergency departments (EAHFE) registry ( 17 ), the high-sensitive (hs)-TnT was recently confirmed to be an optimal biomarker in predicting the 30-days all-come mortality in patients with AHF (with the best cutoff point of 35 ng/l). A similar result was also displayed in one recent multicenter-based study, while the cutoff point was hs-TnT ≥ 43 ng/l ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ideal risk stratification system would identify a subpopulation of patients with similar pathophysiology and clinical presentation at admission, so that treatment may be tailored for each patient. During the past years, researchers from the different regions have made some attempts to discover the prognostic factors in predicting the short-term (28-30-days) or long-term (1-5 years) mortality and readmission in patients with AHF (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Notably, reviewing the recently published literature, elderly age, multimorbidity, high blood urea nitrogen (BUN), serum creatinine, and hypoalbuminemia were significantly associated with the increased risk of AHF-related mortality (2,3).…”
Section: Introductionmentioning
confidence: 99%